Acute upper body complex training with accommodating resistance in collegiate male wrestlers - Jones, M. T.; Oliver, J. M.; Delgado, J.; Robison, C. E. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Upper body power (UB-P) is essential to success in wrestling. Post-activation potentiation, in the form of complex training (CT), has been shown to elicit greater lower body power production in explosive movements when heavy strength movements are performed prior. Accommodating resistance (AR), in the form of bench pressing with chains, has been purported to increase UB-P. Research on UBCT is limited and results are inconclusive. The aim of this study was to determine if acute UB-CT with AR would enhance UB-P. Methods: Participants were 13 wrestlers (20.5 + 1 yr, 174.3 + 4.2 cm, 76.5 + 8.3 kg, 8.5 + 2.6 %BF) with > 1 year of formal strength training. Baseline testing included 3-RM bench press (BP) and %body fat (BF). Prior to testing, participants were randomly assigned to one of two protocols: chain BP or plate BP. One week after baseline testing, participants performed the assigned protocol, which consisted of a warm-up and determination of UB-P during the performance of the plyometric push up (PPU). Participants performed a baseline PPU then benched 1 x 6 reps at 60% 1RM followed by a PPU. After a 3-min rest, participants performed a second set of 1 x 6 reps at 60% 1RM followed by a PPU. All PPU were performed on a force plate for determination UB-P. All were familiar with and performed the PPU regularly in training. Independent samples t-tests were used to analyze physical characteristics and UB strength. A 2 x 3 repeated measures ANOVA was used to analyze UB-P (alpha level: p<0.05). Results: Participants in the plate BP group were older (21.4 + 0.8 yr) than the chain BP group (19.9 + 0.7 yr; p = 0.005). No other differences were observed in physical characteristics or baseline measures. Despite an observable difference in decline of UB-P following initial set (chain BP, -10.9 + 5.3%; plate BP, -17.4 + 5.7%) and set 2 (chain BP, -8.6 + 6.6%; plate BP, +1.0 + 7.2%), no group interaction was observed (p = 0.166). A time effect was observed in which both chain BP and plate BP resulted in a decrease in UB-P following the initial set (-14.1 + 3.9%; p = 0.004), with a return to baseline levels after set 2. Discussion: AR did not result in improvement in UB-P over traditional plate loaded resistances when performing an acute UB-CT. While AR of chains appeared to have attenuated the loss of UB-P following an initial set, traditional plate loaded resistance appeared to attenuate this following a second set. Further testing using a larger sample and crossover is recommended to delineate the influence of the two training methods on UB-P during the PPU.